God vs. the gavel : religion and the rule of law / Marci A. Hamilton ; foreword by Edward R. Becker. - Hamilton, Marci (Cambridge University Press, 2005)
God vs. the Gavel challenges the pervasive assumption that all religious conduct deserves constitutional protection. While religious conduct provides many benefits to society, it is not always benign. The thesis of the book is that anyone who harms another person should be governed by the laws that govern everyone else - and truth be told, religion is capable of great harm. This may not sound like a radical proposition, but it has been under assault since the 1960s. The majority of academics and many religious organizations would construct a fortress around religious conduct that would make it extremely difficult to prosecute child abuse by clergy, medical neglect of children by faith-healers, and other socially unacceptable behaviors. This book intends to change the course of the public debate over religion by bringing to the public's attention the tactics of religious entities to avoid the law and therefore harm others.